TINJAUAN PUSTAKA PENGGUNAAN METODE TRISS UNTUK MENINGKATKAN KUALITAS VISUM ET REFERTUM - Kristian Surbakti, Sony; M. Situmorang, Nasib; Jamnasi, Juli (Jurnal Kedokteran Methodist, 2020)
Background: Trauma is the leading cause of death in adolescents and young adults. A scoring system that can change the quality of trauma into a value is needed in order to predict mortality, compare therapy methods, is a pre- and inter-hospital triage tool, assesses quality improvement and prevention programs, and is a valid evidence tool for law enforcers. .TRISS has been researched and proven to have consistency in assessing the probability of survival of trauma victims in developed countries compared to other injury grade scoring systems Methods: The research method used was a Literature Review, using secondary data. Data collection was carried out using documentation techniques. The research journals used were 5 journals with inclusion criteria, the year of publication of the journal for the last 5 years, the language used was Indonesian and English, with the research subjects namely trauma victims who were assessed by a TRISS score and full text publication. Conclusion: From these studies, it was found that TRISS has a good accuracy in assessing the degree of injury and predicting the outcome of trauma victims. So that the TRISS method can be considered as a tool in assessing the degree of injury to the post mortem and also to find out whether the victim is in danger or not, so that it can improve the quality of VeR in the conclusion section, namely determining the degree of injury to help investigators determine the demands in the trial process.